AquaScouts: ePROs Implemented as a Serious Game for Children With Cancer to Support Palliative Care - Hoffmann, Stefan; Schraut, Robert; Kröll, Thomas; Scholz, Wiebke; Belova, Tatiana; Erhardt, Johann; Gollmer, Daniel; Mauck, Christian; Zacharioudakis, Giorgos; Meyerheim, Marcel; Bonotis, Panos; Kakalou, Christine; et al. (Frontiers in Digital Health, 2021)
MyPal is a European initiative focusing on the use of the electronic patient reported outcome (ePRO) measures to enhance patient engagement in palliative cancer care via digital self-reporting palliative care for patients with cancer. As a part of its approach, MyPal also focuses on pediatric patients, implementing a specific digital health platform including a serious game to facilitate the reporting of the symptoms and overall status regarding their quality of life (QoL). To this end, the reduction of psychological burden related to frequent reporting, a.k.a. as “reporting fatigue” has been identified as a priority. In this study, we present the MyPal-CHILD platform, emphasizing on the serious game named AquaScouts and its key design decisions, while also emphasizing on the respective challenges. More specifically, we provide insights on the participatory design approach applied during the design of the platform and the high-level goals defined based on end-user input. In addition, the validation process applied before the use of the platform under real-world conditions is also presented. Finally, we discuss a number of challenges and the prospects of deploying eHealth interventions to support palliative care.